Proposal for a green tax reform in Cyprus - Zachariadis, Theodoros (My University, 2016)
Cyprus is faced with serious energy and environmental challenges, which may be exacerbated in the future because of climate change. This paper formulates a proposal for a fiscally neutral green tax reform, which can significantly contribute towards the transition to a path of economically and environmentally sustainable development. We propose the gradual implementation of a carbon tax to those sectors that are not subject to the EU Emissions Trading System, a water scarcity charge and a landfill tax for municipal and industrial waste that is disposed of in landfills. We demonstrate the environmental benefits and the increase in public revenues that these taxes will bring about in the medium and long run, and assess the effect of these taxes on firm competitiveness and social equity.
Keywords: Carbon tax; Environmental fiscal reform; Landfill tax; Water charge